Hydrocephalus and primary ciliary dyskinesia. Issue 5 (May 1984) - Greenstone, M A; Jones, R W; Dewar, A; Neville, B G; Cole, P J
Abstract : Primary ciliary dyskinesia was shown in a 12 year old boy with bronchiectasis who had developed hydrocephalus in the neonatal period. The possible relevance of his ciliary abnormality is discussed.